2014
DOI: 10.1039/c4ra06871h
|View full text |Cite
|
Sign up to set email alerts
|

Glass-like thermal conductivity in SrTiO3 thermoelectrics induced by A-site vacancies

Abstract: The introduction of A-site vacancies in SrTiO 3 results in a glass-like thermal conductivity while Nb substituted samples maintain good electrical conductivity. This unexpected result brings SrTiO 3 one step closer to being a high-performing phonon-glass electron-crystal thermoelectric material.Thermoelectric waste heat recovery is widely expected to be an important component of a sustainable energy future. 1 However, affordable and relatively high-performance materials are lacking. Metal oxides are good candi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 25 publications
9
76
0
Order By: Relevance
“…S9, ESI †) are comparable to many of the titanates reported previously, which were doped on either the A or B sites. 27,28,36,37 The observation of high S and σ suggests that the unique band structure of STO, consisting of heavy and light electrons, that allows for high power factors is retained in La0.5Na0.5Ti1-xNbxO3 despite the slight distortion of the structure away from cubic symmetry, consistent with the DFT calculations. A maximum power factor of 0.620.07 mW m -1 K -2 was obtained for La0.5Na0.5Ti0.8Nb0.2O3 at ≈700 K (Fig.…”
Section: J Namesupporting
confidence: 73%
See 1 more Smart Citation
“…S9, ESI †) are comparable to many of the titanates reported previously, which were doped on either the A or B sites. 27,28,36,37 The observation of high S and σ suggests that the unique band structure of STO, consisting of heavy and light electrons, that allows for high power factors is retained in La0.5Na0.5Ti1-xNbxO3 despite the slight distortion of the structure away from cubic symmetry, consistent with the DFT calculations. A maximum power factor of 0.620.07 mW m -1 K -2 was obtained for La0.5Na0.5Ti0.8Nb0.2O3 at ≈700 K (Fig.…”
Section: J Namesupporting
confidence: 73%
“…The observation of a transition from PC to PG behaviour in the Sr1-xLa0.67x0.33xTiO3 system when the A site cation vacancy () content exceeded 20% (x=0.6), significantly increasing MF (Table 1) and resulting in a κ close to κmin from Cahill's model, was rather encouraging. 27 However, the complex defect chemistry of these materials did not allow for electronic doping whilst simultaneously retaining the PG behaviour, as compositions with carrier concentrations sufficient for good thermoelectric response displayed PC thermal conductivity. In order to realise PGEC behaviour in titanates, a strategy is required that combines an equivalent  to those achieved by cation vacancycontaining materials with a structural chemistry that permits electronic doping.…”
mentioning
confidence: 99%
“…2(d), with a peak ZT value up to 0.7 at 1400 K and 0.45 at 1000 K with similar doping level (∼3-4 × 10 20 cm −3 ). Though a little higher in the latter case, our calculated ZT with both experimental range κ agree reasonably well with existing experiments (∼0.2-0.4 at 900 K-1000 K [21][22][23][24]70 ). Complex isoenergy surfaces are favorable for electronic performance as mentioned above.…”
supporting
confidence: 79%
“…A-site vacancies also can lower κ. Particularly, Popuri et al has shown a glass-like thermal conductivity through A-site vacancies and κ = 2.5 W m −1 K −1 can be realized at 1000 K. 23 Recently, Lu and co-workers found high ZT about 0.4 at 973 K with similar low κ = 2.5 W m −1 K −1 from their La-doped and A-site-deficient samples. 24 Importantly, STO has been identified as a material with a corrugated band structure of a form that is particularly beneficial for the electronic part of ZT, but which at the same time is not reasonably described by standard parabolic band models.…”
mentioning
confidence: 99%
See 1 more Smart Citation